Comparison of Ziehl Neelsen Stain, Auramine Rhodamine Stain and Culture Sensitivity of AFB in Routine and Concentrated Pleural Fluid - Thapa, Kamal Raj; Bhattarai, Madhur Dev; Thapa, Anu; Basnet, Tulasa (Nepalese Respiratory Journal, 2022)
Background: Nearly one third of the global population is infected with mycobacterial tuberculosis. Pleural tuberculosis accounts for 20% of extrapulmonary tuberculosis. The diagnosis of tuberculous pleural effusion is difficult because of the low detection rate of different diagnostic tests like microscopy and culture. Current study aimed to compare the detection rate of different tests in non-concentrated and concentrated pleural fluid. Methods: A hospital based prospective cross sectional study was carried out over one year duration in the Medicine Department of Bir Hospital. A total of 52 cases were enrolled. Detailed history taking and physical examination; radiological, hematological and serum biochemical investigations were performed. Thoracocentesis was performed in all the patients; 20 ml pleural fluid was sent for microscopy with ZN and AR staining as well as for AFB culture. Up to 500ml of pleural fluid was heparinized and kept on cylindrical jar for two hours and 50 ml of sediment was also sent for microscopy and culture within one hour. The results obtained were documented and analysis was done. Results: A total of 52 patients, 31 (59.6%) males and 21 (40.4%) females were included. Their mean age of study participants was 38.67 ± 17.71 (range 16-82 years). Common presentations were fever (94.2%), cough (92.3%), breathlessness (84.6%), chest pain (65.4%) and significant weight loss (59.6%). Haemoptysis was present in 13.5%, anemia in 48.1%, enlarged cervical lymph nodes in 5.8% of the patients. The detection rates of ZN stain, AR stain and AFB culture in non-concentrated pleural fluid were 3.8%, 9.6% and 11.5% respectively. The detection rates for the same tests using concentrated pleural fluid of the same patients were 7.7%, 25% and 17.3% respectively. Differences in detection rate with AR stain and AFB culture for non- concentrated and concentrated pleural fluid were statistically significant (p value <0.01). Conclusion: The detection of AFB using microscopy with ZN and AR staining as well as culture in solid media is low. The detection rate was significantly increased by using concentrated pleural fluid sample for microscopy and culture.